The Design and Fabrication of a Ladder-Climbing Robot - Bathula Vineela Rathan; M. Tarun; P. H. J. Venkatesh; Y. Phaneendra (Engineering Proceedings)
Arobotic system refers to a mechanized apparatus, often controllable remotely or programmable via a computer, that is capable of executing various tasks. These machines can be directed by an external control source. While some robots mimic human-like features, most are designed primarily for functionality rather than appearance. They encompass a wide range, from humanoid models like Honda’s Advanced Step in Innovative Mobility and TOSY’s Ping Pong Playing Robot to specialized industrial, medical, or assistance robots, such as those used in surgery. Over time, robotic capabilities have advanced significantly. Modern robots exhibit a broad range of movements and actions, mirroring many tasks performed by humans in daily life. However, despite these advancements, certain crucial operations, such as ladder climbing, which is essential for surveillance, security, and accessing elevated materials, remain challenging for current robotic systems. As part of our project dissertation, we aim to develop a specialized machine capable of climbing ladders. Our design incorporates mechanisms for lower-arm locking, upper-arm advancement and reverse, and upper-arm locking to facilitate this essential function.